DOI: 10.1159/000399507
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy, Hyperplasia and Structural Dilatation of the Human Heart

Abstract: The human heart can exceed the critical heart weight of 500 g in the course of pathological structural adaptation. This abnormal growth is performed not only by an increase in size (hypertrophy) but also in number (hyperplasia) of cardiac muscle cells. Coronary insufficiency, dilatation and chronic heart failure are noted frequently in hearts above this critical heart weight. Chronic heart failure is not a direct consequence of local destruction and scar formation following coronary insufficiency. Unlike acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…Cardiomyocyte adherence to the basement membrane provides a means by which to maintain ventricular size and shape and to transduce the contractile force. Accordingly, reduced cardiomyocyte adhesion may be a mechanism contributing to wall thinning and ventricular dilatation (28,34). However, this is the first study to show estrogen alters integrin expression in the heart.…”
Section: Discussionmentioning
confidence: 78%
“…Cardiomyocyte adherence to the basement membrane provides a means by which to maintain ventricular size and shape and to transduce the contractile force. Accordingly, reduced cardiomyocyte adhesion may be a mechanism contributing to wall thinning and ventricular dilatation (28,34). However, this is the first study to show estrogen alters integrin expression in the heart.…”
Section: Discussionmentioning
confidence: 78%
“…These results agree with the findings of other investigators. By counting the number ofmyocytes across the wall and cross-sectional area ofmyocytes, Linzbach et al (9) showed that ventricular dilatation due to chronic volume overload could not be explained by myocyte stretch but rather by a sliding displacement or slippage of heart layers leading to a decrease in the number of muscle layers in the ventricular wall. Spotnitz et al (10) also reported a strong correlation between changes in wall thickness and changes in transmural cell number but not cell density when studying rat hearts postmortem, passively distended with varying left ventricular volume.…”
Section: Discussionmentioning
confidence: 99%
“…First, necrotic myocytes may rupture or tear, leaving fewer intact myocytes across the wall resulting in wall thinning and cavity dilatation (5,7). Another possibility is that necrotic myocytes are stretched so that cell lengthening and thinning account for the infarct wall thinning (8,9). A final possibility is that wall thinning is due to a geometric rearrangement or a slippage of necrotic myocyte bundles resulting in fewer myocytes across the wall with little or no change in myocyte dimensions (9-1 1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in rats ventricular cellular hypertrophy is associated with a decrease in DNA concentration (Vliegen et al, 1990). By contrast, concomitant increases in both DNA content and ventricular size are indicative of hyperplastic cellular and subcellular 'growth' (Grimm et al, 1970;Linzbach, 1976;Herget et al, 1997;Leeuwenburgh et al, 2008). Hyperplastic growth of the myocardium occurs during normal embryonic and fetal vertebrate development and continues for a short, but indefinite period after hatching or parturition (Li et al, J. Eme and others Mean number of apnoeas Sham Table 2.…”
Section: Removing Crocodilian R-l Cardiac Shunt Causes Ventricular Enmentioning
confidence: 99%